A Comparison of Three Viewing Media for Assessing Dental Arch Relationships in Patients with Unilateral Cleft Lip and Palate. (September 2016) - Zhu, Shiwen; Yang, Yanqi; Gu, Min; Khambay, Balvinder
Objective: To determine the repeatability and reproducibility of using three different viewing media to assess the outcomes of the dental arch relationships of patients with unilateral cleft lip and palate (UCLP) using the GOSLON Yardstick. Design: The GOSLON Yardstick was used to rate the dental arch relationships of 29 patients with UCLP. Three experienced calibrated orthodontists rated the plaster study models, digital study models, and stereoscopic projected three-dimensional (3D) study models separately. There was a minimum of a 1-week interval between each rating session. All three rating sessions were repeated 1 month later. A linear weighted kappa statistic was performed to assess intrarater repeatability and inter-rater reproducibility, as well as the comparison between different viewing media using Kendall's Coefficient of Concordance (Kendall's W) statistic. Results: Intra-rater repeatability was very good for all three viewing media (kappa = 0.83-0.92). Inter-rater reproducibility was good to very good across the three viewing media (kappa = 0.63-0.88). Agreements between plaster study models and digital study models or stereoscopic projected 3D study models were good to very good (kappa = 0.78-0.97 and kappa = 0.72-0.97, respectively), and a Kendall's W ranging from 0.86 to 0.92 ( P < .001). Conclusions: Stereoscopic projected 3D is an alternative method to assess the outcomes of dental arch relationships in patients with cleft lip and palate using the GOSLON Yardstick. It could also be used for viewing patient records, as it recovers the full 3D information captured at the time of the clinical examination.